Historical-Pedagogical Basis Of The Formation Of Ideological Competence (Eurasian Journal of Humanities and Social Sciences, 2025)
This article proposes a theory of ideological knowledge, skills, and competencies related to improving theoretical knowledge about the historical and pedagogical foundations of the formation of ideological competence in future teachers, as well as the formation of professional competence, high moral qualities, ideological maturity, and spiritual and moral values in future teachers.